Effects of metabolic syndrome on pulmonary function tests - Sachdeva, Sidhant; Mohan, Gurinder; Grover, Sunil; Mahajan, Shashi (International Journal of Advances in Medicine, 2021)
Background: Metabolic syndrome is defined as at least three of the five following medical conditions: central obesity(mandatory), high blood pressure, high blood sugar, high serum triglycerides, and low serum high-density lipoprotein (HDL). It has been shown that obesity causes physiological impairment in respiratory system. Methods: In this observational cross sectional study, 60 patients who fulfilled the IDF criteria for metabolic syndrome were included after applying the exclusion criteria and were subjected to spirometry. Results: Most of the patients had a restrictive pattern (43.3%) (n=26). 33.3% (n=20) of the patients had a mixed pattern while 16.7% (n=10) of the patients had a normal picture. Only 6.7% (n=4) of the patients had an obstructive pattern (p<0.001). Mean value of FEV1 had no correlation with increasing number of components of metabolic syndrome whereas mean value of FVC showed a decreasing trend with increasing number of components of metabolic syndrome. Mean FEV1 of the patients was significantly higher in males (1.82±0.71 L) than females (1.24±0.42 L) (p 0.007). Similarly, the mean FVC was significantly higher in males as compared to females. Mean FVC was 2.45 (±0.86) L in males while females had a mean FVC of 1.65 (±0.49) L (p 0.002). Conclusions: In conclusion, Patients with metabolic syndrome have significant impairment of the pulmonary function with restrictive pattern being the most common one.